What is a healthy church? - Dever, Mark.; Dever, Mark. (Wheaton, Ill. : Crossway Books, 2007)
Author Mark Dever seeks to help believers recognize the key characteristics of a healthy church: expositional preaching, biblical theology, and a right understanding of the gospel. Dever then calls us to develop those characteristics in our own churches. By following the example of the New Testament authors and addressing church members from pastors to pew sitters, Dever challenges all believers to do their part in maintaining the local church.
Part 1 : what is a healthy church? -- Part 2 : essential marks of a healthy church -- Part 3 : important marks of a healthy church.
"Reprinted from 9 marks of a healthy church, c2005 by Mark E. Dever"--T.p. verso.
"IX marks"--Cover.
Keywords: Church -- Marks; Church -- Biblical teaching; Choice of church